PEMBELAJARAN MELALUI MEDIA GEOGEBRA DALAM MENGKONSTRUKSI GRAFIK GEOMETRI DENGAN PENEMUAN TERBIMBING - Nur Farida; Rosita Dwi Ferdiani; Tatik Retno Murniasih (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2022)
The purpose of this research is to increase students' understanding in constructing geometric graphs through GeoGebra media with the guided discovery method. The guided discovery method is more often used in learning mathematics because it is teacher oriented so that students are passive and less able to construct mathematical ideas independently. Students only memorize so they are confused about using mathematical concepts. This study uses the type of experimental research. The instrument in this study used student activity observation sheets and learning outcomes tests, while the research sample was students. The application of the guided discovery method using GeoGebra media based on research results can increase student activity and learning outcomes. Student activity increased through GeoGebra media to construct graphs. Based on the results of the student's final test, it was 83.33%. This shows that learning through the GeoGebra media with guided discovery is very effective in constructing student geometry charts on geometry material.